PROBLEMS WITH THE LIBERALIZATION OF CURRENCY POLICY AND WAYS TO SOLVE THEM (Modern education and development, 2025)
This article analyzes the key challenges associated with the liberalization of currency policy and proposes solutions to mitigate the risks. The study reviews the economic consequences of currency liberalization, examines theoretical and empirical perspectives, and suggests strategies for sustainable monetary policy management. By evaluating case studies from various economies, the research identifies best practices that can be adapted to different financial environments.